Vitamin B and Essential Minerals Contents of Mixed Solid State Fermented Millet (Steria italic) and Bengal Gram by Rhizopus oligosporus (Bangladesh Journal of Scientific and Industrial Research, 2011)
Mixed solid state fermentation by Rhizopus oligosporus on nutritional and anti-nutritional factors of dehulled cereal Seteria italica (millet or kaon) and legume Cicer arietinum (Bengal gram or chola or chick pea) were studied. The fermentation method used was similar to the traditional fermentation procedures used in the preparation of tempeh from Soybean in the orient. The duration of fermentation was 24 hours at 37°C under controlled laboratory conditions. In this study, the vitamin B content especially thiamine, niacin and vitamin B6 (Pyridoxine) were estimated after 24 hours of fermentation of (50:50), (60:40) and 75:25) ratios of mixed Seteria italica (millet or kaon) and Cicer arietinum (Bangal gram or chola or chick pea) respectively. After 24 hours fermentation, thiamine content increased significantly, when compared with the thiamine content of raw state. The content of thiamine, niacin and vitamin B6 in the fermented form were also increased when compared these with soaked and steamed state respectively. Incase of minerals after fermentation iron, copper, calcium, sodium and potassium contents were decreased when compared these with raw state. The contents of iron, copper calcium, sodium and potassium in the fermented form were also decreased when compared with the iron, copper, calcium, sodium and potassium contents of soaked and steam state respectively. The nutritional factors like B vitamins (thiamine, niacin, and vitamin B6) were increased significantly however, minerals were decreased. Our results suggest that tempeh can be prepared with millet and Bengal gram may be a good source of vitamin B6 for children and aged people. Keywords: Rhizopus oligosporus; Tenpeh; Bengal gram; Vitamin B; Essential minerals DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8098 Bangladesh J. Sci. Ind. Res. 46(1), 1-8, 2011